An association between the vitamin D receptor BsmI polymorphism and the incidence of placental insufficiency in women at high risk of infection - Manasova, G.S.; Artyomenko, V.V.; Didenkul, N.V.; Kuzmina, N.V.; Pollacco, J. (REPRODUCTIVE ENDOCRINOLOGY, 2023)
Research objectives: the study examined the effect of the BsmI polymorphism of the gene encoding vitamin D receptors (A > G, rs1544410) on human placental dysfunction. Materials and methods. An observational-analytical study carried out according to the «case-control» principle. The study was conducted in two maternity hospitals in the city of Odessa, Ukraine over the same period of time. Special enzyme immunoassay and molecular genetic studies were carried out at the LLC «Diagnostic Center Evgenika» in Odessa. The intervention group included a total of 56 pregnant women aged 18 to 40 with high infectious risk and signs of placental dysfunction. The control consisted of 40 apparently healthy women with an uncomplicated pregnancy. The 25(OH)D blood level was determined by the ELISA method whereas the gene polymorphism encoding vitamin D receptors was determined by PCR. Results. The number/percentage of women with placental dysfunction in the intervention and control groups respectively, their hydroxyvitamin D levels as well as the genotypes expressed was investigated. In placental dysfunction patients, vitamin D level was significantly lower than in healthy individuals. There was a direct correlation between the placental dysfunction frequency and the A/G genotype. In vitamin D deficiency, the heterozygous A/G genotype for vitamin D receptor gene polymorphic locus increased the risk of development of placental dysfunction by 3.6 times. Conclusions. Vitamin D deficiency may increase the risk of placental dysfunction. For a more complete understanding between vitamin D receptor gene polymorphism and placental dysfunction, it is necessary to study all four vitamin D receptors polymorphisms with 25(OH)D levels correlations as well as polymorphisms of genes CYP27B1 and CYP24A1.